Dosimetric and radiobiological impact of intensity modulated proton therapy and RapidArc planning for high‐risk prostate cancer with seminal vesicles. Issue 1 (11th May 2016) - Rana, Suresh; Cheng, ChihYao; Zhao, Li; Park, SungYong; Larson, Gary; Vargas, Carlos; Dunn, Megan; Zheng, Yuanshui
Abstract: Introduction: The purpose of this study was to evaluate the dosimetric and radiobiological impact of intensity modulated proton therapy (IMPT) and RapidArc planning for high‐risk prostate cancer with seminal vesicles. Methods: Ten high‐risk prostate cancer cases were included in this retrospective study. For each case, IMPT plans were generated using multiple field optimisation (MFO) technique (two fields) with XiO treatment planning system (TPS), whereas RapidArc plans were generated using double‐arc technique (two full arcs) with Eclipse TPS. IMPT and RapidArc plans were optimised for a total prescription dose of 79.2 Gy (relative biological effectiveness (RBE)) and 79.2 Gy, respectively, using identical dose–volume constraints. IMPT and RapidArc plans were then normalised such that at least 95% of the planning target volume (PTV) received the prescription dose. Results: The mean and maximum PTV doses were comparable in IMPT plans (80.1 ± 0.3 Gy (RBE) and 82.6 ± 1.0 Gy (RBE) respectively) and RapidArc plans (80.3 ± 0.3 Gy and 82.8 ± 0.6 Gy respectively) with P = 0.088 and P = 0.499 respectively. The mean doses of the rectum and bladder were found to be significantly lower in IMPT plans (16.9 ± 5.8 Gy (RBE) and 17.5 ± 5.4 Gy (RBE) respectively) when compared to RapidArc plans (41.9 ± 5.7 Gy and 32.5 ± 7.8 Gy respectively) with P < 0.000 and P < 0.000 respectively. For the rectum, IMPT produced lower V30 (21.0 ± 9.6% vs. 68.5 ± 10.0%; P < 0.000), V50 (14.3 ± 5.8% vs. 45.0 ± 10.0%; P < 0.000) and V70 (6.9 ± 3.4% vs. 12.8 ± 3.6%; P < 0.000) compared to RapidArc. For the bladder, IMPT produced lower V30 (23.2 ± 7.0% vs. 50.9 ± 15.6%; P < 0.000) and V50 (16.6 ± 5.4% vs. 25.1 ± 9.6%; P = 0.001), but similar V70 (9.7 ± 3.5% vs. 10.5 ± 4.2%; P = 0.111) compared to RapidArc. RapidArc produced lower mean dose for both the right femoral head (19.5 ± 4.2 Gy vs. 27.4 ± 4.5 Gy (RBE); P < 0.000) and left femoral head (18.0 ± 4.3 Gy vs. 28.0 ± 5.6 Gy (RBE); P < 0.000). Both IMPT and RapidArc produced comparable bladder normal tissue complication probability (NTCP) (0.6 ± 0.2% vs. 0.5 ± 0.2%; P = 0.152). The rectal NTCP was found to be lower using IMPT (0.8 ± 0.7%) than using RapidArc (1.7 ± 0.7%) with P < 0.000. Conclusion: Both IMPT and RapidArc techniques provided comparable mean and maximum PTV doses. For the rectum, IMPT produced better dosimetric results in the low‐, medium‐ and high‐dose regions and lower NTCP compared to RapidArc. For the bladder, the NTCP and dosimetric results in the high‐dose region were comparable in both sets of plans, whereas IMPT produced better dosimetric results in the low‐ and medium‐dose regions. Abstract : This paper investigates the dosimetric and radiobiological impact of intensity modulated proton therapy (IMPT) and RapidArc planning for high‐risk prostate cancer with seminal vesicles.